Learning letters - Blue, Bubble (United Kingdom : Blue Bubble books Ltd, 2022)
This book is designed to support you in your child's early years development. We value the importance of learning and recognize how children learn best through fun activities and play. You will find simple exercises for you to help your child, combined with an element of fun which we know will keep them engaged and help develop confidence. The activities in this book are part of a series of titles designed to assist with learning to recognize, say out loud and write letters and words. This book supports your child in learning and developing fine motor skills and pen control, which are necessary to be able to develop these shapes and forms into letters and words.
Location: 2C
Keywords: Activity book